Most Readmissions Following Ankle Fracture Surgery Are Unrelated to Surgical Site Issues: An Analysis of 5056 Cases. Issue 2 (7th April 2017) - Fu, Michael C.; Young, Kelsey; Cody, Elizabeth; Schairer, William W.; Demetracopoulos, Constantine A.; Ellis, Scott J.
Background: Ankle fracture surgeries are generally safe and effective procedures; however, as quality-based reimbursement models are increasingly affected by postoperative readmission, we aimed to determine the causes and risk factors for readmission following ankle fracture surgery. Methods: Ankle fracture cases were identified from the prospectively collected American College of Surgeons National Surgical Quality Improvement Program from 2013 to 2014. Demographics, comorbidities, and fracture characteristics were collected. Rates of 30-day adverse events and readmissions were determined as well as the causes for readmission. Multivariable logistic regression analyses were performed to identify risk factors associated with having any adverse events and being readmitted within 30 days of surgery. Results: There were 5056 patients included; 167 (3.3%) were open fractures. The rate of any postoperative adverse event was 5.2%. There were 116 unplanned readmissions, with a readmission rate of 2.3%. Of the 116 unplanned readmissions, 49 (42.2%) were for reasons related to the surgery or surgical site, with the most common causes being deep surgical site/hardware infections (12.9%), superficial site infections (11.2%), and wound disruption (6.9%). Most readmissions were for reasons unrelated to the surgical site (51.7%), including cardiac disorders (8.6%), pulmonary disorders (7.8%), and neurological/psychiatric disorders (6.9%). The cause of readmission was unknown for 6% of readmissions. With multivariable logistic regression, the strongest risk factors for readmission were a history of pulmonary disease (odds ratio [OR], 2.29), American Society of Anesthesiologists (ASA) class ≥3 (OR, 2.28), and open fractures (OR, 2.04) (all P < .05). Conclusion: In this cohort of 5056 ankle fracture cases, 2.3% of patients were readmitted within 30 days, with at least 51.7% of all unplanned readmissions due to causes unrelated to the surgery or surgical site. Predictors of readmission included a history of pulmonary disease, higher ASA class, and open fractures. Based on these findings, we advocate close medical follow-up with nonorthopaedic providers after discharge for high-risk patients. Level of Evidence: Level III.